1960
DOI: 10.1152/ajplegacy.1960.199.6.987
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid metabolism in fetal and newborn sheep

Abstract: The metabolism of free fatty acids (FFA) was studied in the term ewe, sheep fetus and newborn lamb. The concentration of FFA is about 10 times greater and the concentration of triglyceride fatty acids (TGFA) 2 1/2 times greater in maternal than in fetal plasma. After intravascular administration of palmitic acid-1-C14 complexed to homologous albumin, the initial rates of disappearance of FFA radioactivity from maternal and fetal circulations were similar, with half-times of approximately 2 minutes. Radioactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(34 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…It appeared that, in contrast with the nonruminant, the ruminant placenta was relatively impermeable to 18:2n6 and 18:3n3 (Hansen et al, 1964;Leat, 1966). In addition, it has been shown that the placentas of rats, rabbits and sheep are relatively impermeable to plasma cholesterol and phospholipids, whereas plasma non-esterified FA can pass the placental barrier into the fetus (Duyne et al, 1960;Popjak, 1954;McBride and Korn, 1964). Leat (1966) reported that sow-plasma non-esterified FA contained 4.8-10:0 times more 18:2n6 than ruminants and suggested that less 18:2n6 acid would pass into the ruminant fetus than into the non-ruminant fetus in this way.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that, in contrast with the nonruminant, the ruminant placenta was relatively impermeable to 18:2n6 and 18:3n3 (Hansen et al, 1964;Leat, 1966). In addition, it has been shown that the placentas of rats, rabbits and sheep are relatively impermeable to plasma cholesterol and phospholipids, whereas plasma non-esterified FA can pass the placental barrier into the fetus (Duyne et al, 1960;Popjak, 1954;McBride and Korn, 1964). Leat (1966) reported that sow-plasma non-esterified FA contained 4.8-10:0 times more 18:2n6 than ruminants and suggested that less 18:2n6 acid would pass into the ruminant fetus than into the non-ruminant fetus in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamics of lipolysis studies in vitro in adipose tissue from neonates show that lipolysis increases rapidly from the moment of birth, reaches its maximum within a few hours, and then gradually decreases [22,25]. The biochemical mechanism of elevated lipid mobilization in human neonates is not known exactly [29,40], but in newborn lambs activity of the sympathetic nervous system is increased at this time [38]. The basal release of glycerol from adipose cell suspensions has been found to be higher in the first hours of extrauterine life than at any other time during the first 10 days of life, yet response to norepinephrine was less [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…that, as in sheep [26], guinea pig [7,10], rabbit [25], rat Injection of labeled palmitic acid parenterally to the […”
Section: Introductionmentioning
confidence: 99%